PKM pendekatan pembelajaran kontekstual pada Guru- Guru Sekolah Dasar Negeri No. 80 Kota Parepare - Yonathan Saba; Pasinggi Pasinggi; Ritha Tuken (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
Understanding contextual reading is an observation, initiative, tried, some of them to hear, follow, instructions.Contextual learning, teachers guide students weeks to find answers, make notes and conclusions from the book source, anddisplay the pictures show an example. From my observation the writer, colleague and self-reflection, then the identified problemlearning. Based on the problems experienced by primary teachers about teaching in class, then to overcome itpenyuluhmengambil inisyatif with classroom teachers to identify problems in the form of improved learning with a focus onefforts to "Improving Learning Outcomes in Learning IPS, PKN, Mathematics And according to disciplines research team.Through Contextual Learning teachers SDN No 80 Edge said Pare Pare "In the extension described several contextual learningapproach that will simplify the process of learning and how teachers involve students in learning and teaching process inaccordance with the steps defined contextual learning. In contextual learning, teachers' task is to help students to explore and gainknowledge procedurally. For example how to lead students to read, underline the important things and then poured it in aworking paper from a source of learning, such as textbooks, or other learning resources. Also a teacher can give examples of howthe techniques of discussion and good communication, an example of simulation techniques, meetings and so forth. Furtherexplained in the frame of mind. Expected outcomes are the teachers SDN No.80 Edge Parepare after following this extension areexpected to follow up with the implement in their respective schools and improve learning in the classroom.